1991
DOI: 10.1038/349609a0
|View full text |Cite
|
Sign up to set email alerts
|

GABAB autoreceptors regulate the induction of LTP

Abstract: Understanding the mechanisms involved in long-term potentiation (LTP) should provide insights into the cellular and molecular basis of learning and memory in vertebrates. It has been established that in the CA1 region of the hippocampus the induction of LTP requires the transient activation of the N-methyl-D-aspartate (NMDA) receptor system. During low-frequency transmission, significant activation of this system is prevented by gamma-aminobutyric acid (GABA) mediated synaptic inhibition which hyperpolarizes n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

20
307
2
11

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 578 publications
(342 citation statements)
references
References 23 publications
20
307
2
11
Order By: Relevance
“…Indeed, exogenous BDNF promotes the induction of LTP in the young hippocampus; in turn, endogenous BDNF is suggested to be involved in the triggering mechanism of LTP in the adult (Figurov et al, 1996). Disinhibition induced by BDNF will participate in the induction of LTP, because elimination of GABAergic hyperpolarizing influence relieves voltage-dependent Mg 2ϩ block of NMDA receptor-channel and facilitates the induction of LTP (Davies et al, 1991;Mott and Lewis, 1991). This also is supported by the results of mutant mice lacking BDNF (Korte et al, 1995), which showed significantly reduced LTP in the hippocampus.…”
Section: Inhibition Of Gaba a Receptor-mediated Ipscs By Bdnfmentioning
confidence: 99%
“…Indeed, exogenous BDNF promotes the induction of LTP in the young hippocampus; in turn, endogenous BDNF is suggested to be involved in the triggering mechanism of LTP in the adult (Figurov et al, 1996). Disinhibition induced by BDNF will participate in the induction of LTP, because elimination of GABAergic hyperpolarizing influence relieves voltage-dependent Mg 2ϩ block of NMDA receptor-channel and facilitates the induction of LTP (Davies et al, 1991;Mott and Lewis, 1991). This also is supported by the results of mutant mice lacking BDNF (Korte et al, 1995), which showed significantly reduced LTP in the hippocampus.…”
Section: Inhibition Of Gaba a Receptor-mediated Ipscs By Bdnfmentioning
confidence: 99%
“…The effects of GABA B R activation on the network are dominated by inhibition leading to an overall dampened population activity. However, if GABAergic interneurons are effected dominantly, as observed for example, during high-frequency stimulation, GABA B R activation can produce disinhibition in principal cells (12,13). Accordingly, the role of GABA B Rs in epilepsy and seizure generation remains ambiguous.…”
mentioning
confidence: 99%
“…As such, the question still remains as to whether pharmacologically distinguishable GABA B receptors are activated by synaptically released GABA. The answer to this question is important as it will provide a better understanding of the normal physiological and pathological roles that GABA B receptors play in vivo, most notably in terms of their e ects on mnemonic processing (Olpe & Karlsson, 1990;Davies et al, 1991;Mott & Lewis, 1991;Mondadori et al, 1993;Olpe et al, 1993b) and absence epilepsy (Liu et al, 1992;Hosford et al, 1992). Ultimately, this may lead to the development of a new generation of compounds that through targeting of speci®c GABA B receptor populations may be more e cacious in treating speci®c disease states.…”
mentioning
confidence: 99%